Factors contributing to students’ satisfaction in online learning: A proposed framework for CLIL classes - Khoiriyah Khoiriyah; Muhammad Firza Thoriq Sholahuddin; Ananta Benny Dele Bintang (Universitas Muhammadiyah Malang, 2025)
This research explores the factors contributing to students' satisfaction in online learning, particularly in Content and Language Integrated Learning (CLIL) classes. Through a literature review, three primary factors were identified as crucial determinants of student satisfaction: online self-efficacy, self-regulated learning, and online interaction. Online self-efficacy encompasses students' confidence in their abilities to complete online courses, communicate with peers and instructors, and manage course technologies. Self-regulated learning strategies, such as strategic planning, time management, and help-seeking, positively influence both student satisfaction and academic achievement. The quality and type of online interactions, including teacher-student, student-student, and student-content interactions, significantly impact satisfaction levels. The findings suggest that effective online learning environments should foster student engagement through quality interactions, provide adequate technological support, and promote self-directed learning strategies. The research also highlights the importance of classroom climate and online learning in enhancing student satisfaction. Educational institutions should prioritize enhancing the quality of online interactions, training educators in effective online teaching practices, and expanding technological resources to better meet student needs. Future research should employ mixed methods to gain deeper insights into student experiences and satisfaction, contributing to a comprehensive understanding of online learning dynamics.